Answer:
(f * g)(x) = 4x^3 - x^2
![4x^(3)-x^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4eae275iifnh0ng0i5cjbjxe35iplnutno.png)
Explanation:
We have been given the following functions;
f(x) = 4x - 1
g(x) = x^2
We are required to determine;
(f * g)(x)
This simply means we shall be finding the product of the two functions given;
(f * g)(x) = f(x)*g(x)
(f * g)(x) = x^2 * (4x - 1 )
we open the brackets by multiplying each term by x^2
(f * g)(x) = x^2(4x) + x^2(-1)
(f * g)(x) = 4x^3 - x^2